Massive boulders shifted along the coast of Guantánamo, Cuba, during Hurricane Matthew (2016) - Engel, Max; Pupo, Felipe Matos; Ortega, Zadiérik Hernández; Brill, Dominik (Erdkunde, 2025)
Hurricane Matthew struck the province of Guantánamo in southeastern Cuba in 2016 by making landfall as the first and only hurricane reaching category 4 in documented history. We surveyed transport path, distance and mode of coastal boulder deposits (CBD) after the event at three coastal sites and compared them with the pre-Matthew boulderscape, which reflects the effects of extreme-wave events on millennial time scales. The application of a dimensionless analytical framework comparing elevation, CBD size and wave climate with a global dataset of storm-transported CBD shows that boulder transport during Matthew is at the uppermost possible limit, while larger boulders that remained inactive hint to even more intense hurricanes or a large tsunami in the prehistoric past. Most observations support typical patterns of storm-transported CBD in carbonate environments, such as a source at the cliff edge, preferential sourcing and clustering at shoreline indentations and a stepwise movement inland during multiple storm events. The study shows that Hurricane Matthew is not unique in Guantánamo in terms of intensity on larger, prehistoric time scales. At the same time, recurrence intervals of highest-category hurricanes in this region may decrease with ongoing climate change prompting the need to use the inland distribution of CBD plus additional buffer as minimum setback zones in coastal hazard management.